Pathophysiology of cardiotoxicity induced by nonanthracycline chemotherapy. (May 2016) - Madeddu, Clelia; Deidda, Martino; Piras, Alessandra; Cadeddu, Christian; Demurtas, Laura; Puzzoni, Marco; Piscopo, Giovanna; Scartozzi, Mario; Mercuro, Giuseppe
Abstract : The risk and mechanism of chemotherapy-induced cardiotoxicity (CTX) vary depending on the type and intensity of the anticancer regimen. Myriad chemotherapeutic drugs produce adverse cardiovascular effects such as arterial hypertension, heart failure, and thromboembolic events. Among the numerous classes of these drugs, anthracyclines have been studied most extensively because of their overt cardiovascular effects and the high associated incidence of heart failure. However, CTX might also be caused by other types of chemotherapeutic agents, including alkylating agents (cyclophosphamide, ifosfamide), platinum agents, antimetabolites (5-fluorouracil, capecitabine), antibiotics (mitoxantrone, mitomycin, bleomycin), and antimicrotubule agents (taxanes). Here, we review the incidence, clinical impact, and potential mechanisms of CTX associated with nonanthracycline chemotherapy used for cancer patients. The published data support a marked increase in CTX risk, particularly with certain drugs such as 5-fluorouracil and cisplatin. Each anticancer regimen is associated with distinct modes of heart damage, both symptomatic and asymptomatic. However, the underlying mechanisms of CTX have been established only in a few cases, and only few nonanthracycline chemotherapeutics (mitoxantrone, mitomycin, ifosfamide) act through a recognizable mechanism and show a predictable dose dependence. Lastly, nonanthracycline chemotherapy can induce both chronic lesions, such as systolic dysfunction, and acute lesions, such as the ischemia that occurs within hours or days after treatment. An increased understanding of the incidence, mechanisms, and potential therapeutic targets of CTX induced by various nonanthracycline chemotherapeutic agents is clearly required.